PENGEMBANGAN PERPUSTAKAAN DIGITAL BERINKLUSI SOSIAL DALAM EKOSISTEM DIGITAL BERBASIS MULTIKULTURAL INDONESIA - Hartono, Hartono (Jurnal El-Pustaka, 2020)
In the history of civilization, libraries are organizations that grow and develop organisms that are able to adapt to the times. A number of factors related to library development in the digital ecosystem are the issue of the industrial revolution of era 4.0 marked by the Internet of think, artificial intelligence, big data, and the community of era 5.0 based on the era of humanity-based society. The transformation of libraries in the new era has shifted the role of digital libraries in developing digital libraries in socially inclusive digital ecosystems. In a digital ecosystem, a digital library has various advantages that will support the tasks of digital library professionals including the ability to provide information, organize, store, manage information, and disseminate information while preserving information. However, the demands of the era should not affect the management of the digital library itself. Then in universally, all types of digital libraries carry functions as an educational center, repository center, research center, information center, and cultural center. Then each type of digital library has social inclusion to perform the five functions. The role of digital libraries in developing social inclusion with a multicultural perspective in Indonesia, can play the following roles: (a) understanding cultural diversity in digital libraries; (b) appreciates the collection of digital libraries to meet the diverse information needs of users; (c) develop human resources professionally; (d) interact with information technology fluently; and (e) building critical awareness of the regulation of digital library access policies.